In Search of a Cure for Sepsis: Taming the Monster in Critical Care Medicine - Okeke, Emeka B. (J Innate Immun, 2016)
In spite of over half a century of research, sepsis still constitutes a major problem in health care delivery. Although advances in research have significantly increased our knowledge of the pathogenesis of sepsis and resulted in better prognosis and improved survival outcome, sepsis still remains a major challenge in modern medicine with an increase in occurrence predicted and a huge socioeconomic burden. It is generally accepted that sepsis is due to an initial hyperinflammatory response. However, numerous efforts aimed at targeting the proinflammatory cytokine network have been largely unsuccessful and the search for novel potential therapeutic targets continues. Recent studies provide compelling evidence that dysregulated anti-inflammatory responses may also contribute to sepsis mortality. Our previous studies on the role of regulatory T cells and phosphoinositide 3-kinases in sepsis highlight immunological approaches that could be explored for sepsis therapy. In this article, we review the current and emerging concepts in sepsis, highlight novel potential therapeutic targets and immunological approaches for sepsis treatment and propose a biphasic treatment approach for management of the condition.